The Cambridge companion to fantasy literature - James, Edward, 1947-; Mendlesohn, Farah (Cambridge : Cambridge University Press, 2012)
'Fantasy is a creation of the Enlightenment and the recognition that excitement and wonder can be found in imagining impossible things. From the ghost stories of the Gothic to the zombies and vampires of twenty-first-century popular literature, from Mrs Radcliffe to Ms Rowling, the fantastic has been popular with readers. Since Tolkien and his many imitators, however, it has become a major publishing phenomenon. In this volume, critics and authors of fantasy look at the history of fantasy since the Enlightenment, introduce readers to some of the different codes for the reading and understanding of fantasy and examine some of the many varieties and subgenres of fantasy; from magical realism at the more literary end of the genre, to paranormal romance at the more popular end. The book is edited by the same pair who edited The Cambridge Companion to Science Fiction (winner of a Hugo Award in 2005)'--
'Fantasy is not so much a mansion as a row of terraced houses, such as the one that entranced us in C. S. Lewis's The Magician's Nephew with its connecting attics, each with a door that leads into another world. There are shared walls, and a certain level of consensus around the basic bricks, but the internal decor can differ wildly, and the lives lived in these terraced houses are discrete yet overheard. Fantasy literature has proven tremendously difficult to pin down. The major theorists in the field - Tzvetan Todorov, Rosemary Jackson, Kathryn Hume, W. R. Irwin and Colin Manlove - all agree that fantasy is about the construction of the impossible whereas science fiction may be about the unlikely, but is grounded in the scientifically possible. But from there these critics quickly depart, each to generate definitions of fantasy which include the texts that they value and exclude most of what general readers think of as fantasy. Most of them consider primarily texts of the nineteenth and early twentieth century. If we turn to twentieth-century fantasy, and in particular the commercially successful fantasy of the second half of the twentieth century, then, after Tolkien's classic essay,'On Fairy Stories', the most valuable theoretical text for taking a definition of fantasy beyond preference and intuition is Brian Attebery's Strategies of Fantasy (1992)'--
Machine generated contents note: Introduction Edward James and Farah Mendlesohn; Part I. Histories: 1. Fantasy from Dryden to Dunsany Gary K. Wolfe; 2. Gothic and horror fiction Adam Roberts; 3. American fantasy, 1820-1950 Paul Kincaid; 4. The development of children's fantasy Maria Nikolajeva; 5. Tolkien, Lewis, and the explosion of genre fantasy Edward James; Part II. Ways of Reading: 6. Structuralism Brian Attebery; 7. Psychoanalysis Andrew M. Butler; 8. Political readings Mark Bould and Sherryl Vint; 9. Modernism and postmodernism Jim Casey; 10. Thematic criticism Farah Mendlesohn; 11. The languages of the fantastic Greer Gilman; 12. Reading the fantasy series Kari Maund; 13. Reading the slipstream Gregory Frost; Part III. Clusters: 14. Magical realism Sharon Sieber; 15. Writers of colour Nnedi Okorafor; 16. Quest fantasies W. A. Senior; 17. Urban fantasy Alexander C. Irvine; 18. Dark fantasy and paranormal romance Roz Kaveney; 19. Modern children's fantasy Charlie Butler; 20. Historical fantasy Veronica Schanoes; 21. Fantasies of history and religion Graham Sleight.
Includes bibliographical references (p. 257-261) and index.
Includes bibliographical references and index.
Keywords: Fantasy literature, English -- History and criticism; Fantasy literature, American -- History and criticism; Fantasy literature -- History and criticism -- Theory, etc; Fantasy literature -- Appreciation